POLA UNSUR INTRINSIK DAN SUBGENRE HOROR PADA UTAS HOROR TWITTER INDONESIA TAHUN 2021: Pattern of Intrinsic Elements and Subgenres of Indonesian Horror Threads on Twitter in 2021 - Kristophorus Divinanto Adi Yudono (Kantor Bahasa Provinsi Maluku, 2023)
Abstract This study aimed to describe the pattern of intrinsic elements and subgenres of Indonesian horror threads on Twitter social media in 2021.The Intrinsic analyzing is performed by reading each horror thread to find patterns of themes, plots, characters and characterizations, settings, points of view, and moral elements. The Analysis of the horror subgenre was carried out based on the classification that ViktoÌria ProhaÌszkovaÌ carried out. The results of the intrinsic analysis show that there is a pattern of intrinsic elements of horror threads published in 2021. The horror theme pattern is the theme of pesugihan practices. The plot pattern used is the forward plot. The character & characterization pattern is the existence of parental figures who understand magical science. The time-setting pattern is that horror events always occur at night. The setting of the place that is always used in the story is an abandoned place. The dynamics of lower-class society trying to achieve economic well-being became a pattern of social background. The viewpoint pattern used is the first-person point of view. The pattern of moral values that always appears is the observance of the norms of society. Based on the analysis of the horror subgenre, Twitter Indonesia horror threads in 2021 take in the occult horror subgenre. Keywords: intrinsic; subgenre; Twitter; thread; horror Â Abstrak Kajian ini dilakukan dengan tujuan mendeskripsikan pola unsur intrinsik dan subgenre utas-utas horor Indonesia pada media sosial Twitter tahun 2021. Analisis intrinsik dilakukan dengan membaca setiap utas horor untuk menemukan pola tema, plot, tokoh dan penokohan, latar, sudut pandang, dan unsur moral. Analisis subgenre horor dilakukan berdasarkan klasifikasi yang dilakukan ViktoÌria ProhaÌszkovaÌ. Hasil analisis instrinsik menunjukkan terdapat pola persamaan unsur intrinsik utas horor yang diterbitkan pada tahun 2021. Pola tema horror ialah tema praktik pesugihan. Pola plot yang digunakan adalah plot maju. Pola tokoh & penokohan ialah keberadaan tokoh orang tua yang memahami ilmu magis. Pola latar waktu ialah kejadian horor selalu terjadi pada malam hari. Latar tempat yang senantiasa digunakan dalam cerita ialah tempat terbengkalai. Dinamika masyarakat kelas bawah yang berusaha mencapai kesejahteraan ekonomi menjadi pola latar belakang sosial. Pola sudut pandang yang digunakan adalah sudut pandang orang pertama. Pola nilai moral yang senantiasa muncul adalah ketaatan terhadap norma-norma masyarakat. Berdasarkan analisis subgenre horor, utas-utas horor Twitter Indonesia tahun 2021 masuk pada subgenre horor occult. Kata-kata kunci: intrinsik; subgenre; Twitter; utas; horor